First record of Caryophyllia smithii in the central southern North Sea: artificial reefs affect range extensions of sessile benthic species. (29th September 2015) - Coolen, Joop W.P.; Lengkeek, Wouter; Lewis, Gareth; Bos, Oscar G.; Van Walraven, Lodewijk; Van Dongen, Udo
Abstract : In the North Sea, observations of the solitary coral Caryophyllia smithii are mostly limited to the north-east coast of the United Kingdom including the Shetland and Orkney islands. To date, C. smithii has not been reported from far offshore locations in the North Sea south of 57.7°N. Distribution of this species appears limited by the restricted availability of natural hard substrata in the central southern North Sea. There are, however, many artificial hard substrata in this area in the form of shipwrecks and offshore oil and gas installations. These may provide stepping stones for C. smithii to expand its distribution. Here we report the first sighting of C. smithii in the central southern North Sea on an unidentified wreck on the Dogger Bank. This is the first offshore observation of any hard coral in the central southern North Sea.